Parental Experiences in Caring for Children with Thalassemia Major in Tangerang: A Phenomenological Study - Fangidae, Erniyati; Lestari, Dwi Puji; Hutagalung, Grace Yenni A; Sigarlaki, Melisa Constantine (Nursing Current: Jurnal Keperawatan, 2025)
Introduction: Thalassemia major can lead to significant physical, psychological, and social challenges that reduce a child’s quality of life and increase the burden on the family. Parents play a crucial role in the care of children with thalassemia major, however, they often face significant challenges. This study aimed to explore the lived experiences of parents whose children have been diagnosed with thalassemia major at a private hospital in Tangerang. Methods: This research employed a descriptive phenomenological qualitative design conducted between October and November 2024. Participants were selected through purposive sampling and included 10 parents of children with thalassemia major receiving care at a private hospital in Tangerang. Data were collected through in-depth interviews guided by seven open-ended questions. All interviews were audio-recorded and transcribed verbatim.Chi Data analysis was conducted using Colaizzi’s 1978 method. Results: The analysis revealed four major themes: 1). Psychological upheaval, 2). Burdens of caring, 3). Affirmative attitudes, and 4). Psychosocial support for the child. Conclusion: This study highlights the significant experiences of parents caring for children with thalassemia major. Recommendation: Understanding parents' experiences can help nurses and healthcare providers offer more comprehensive support and develop holistic interventions that assist parents in adapting more effectively and improving their overall quality of life.